Targeting the Metabolic Microenvironment of Tumors - Bailey, Kate M. (2012)
The observation of aerobic glycolysis by tumor cells in 1924 by Otto Warburg, and subsequent innovation of imaging glucose uptake by tumors in patients with PET-CT has incited a renewed interest in the altered metabolism of tumors. As tumors grow in situ, a fraction of it is further away from their blood supply, leading to decreased oxygen concentrations (hypoxia), which induces the hypoxia response pathways of HIF1α, mTOR and UPR. In normal tissues, these responses mitigate hypoxic stress and induce neo-angiogenesis. In tumors, these pathways are dysregulated and lead to decreased perfusion and exacerbation of hypoxia as a result of immature and chaotic blood vessels. Hypoxia selects for a glycolytic phenotype and resultant acidification of the tumor microenvironment, facilitated by upregulation of proton transporters. Acidification selects for enhanced metastatic potential and reduced drug efficacy through ion trapping. In this review, we provide a comprehensive summary of pre-clinical and clinical drugs under development for targeting aerobic glycolysis, acidosis, hypoxia and hypoxia-response pathways. Hypoxia and acidosis can be manipulated, providing further therapeutic benefit for cancers that feature these common phenotypes.